Maximal Homomorphism in Fundamental Theorem of Homomorphism Semiring - Hardiansyah, Riski Ryan; Wardati, Khurul; Riyanto, Muhamad Zaki (Proceeding International Conference on Science and Engineering, 2017)
Semiring is a generalization of ring. Some concepts in ring can be developed in semiring. The contructions of quotient semiring requires a specific ideal, namely Q-ideal. Different to the ring theory, the fundamental theorems of homomorphism on semiring needs a concept of maximal homomorphism, science the kernel of any maximal homomorphism is always Q-ideal.